1989
DOI: 10.1093/schbul/15.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Minor Physical Anomalies in Schizophrenia

Abstract: This study was conducted to investigate the value of using physical anomalies (PAs) to evaluate early prenatal injury in schizophrenia. PAs are minor abnormalities in development of the head, hands, and feet that are presumably associated with insult during the first trimester. Sixty-seven schizophrenic inpatients and 88 normal controls were evaluated for PAs. The schizophrenic patients showed significantly more anomalies than the controls. The difference remained significant even when patients were compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
121
0
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(138 citation statements)
references
References 27 publications
14
121
0
3
Order By: Relevance
“…Recent studies have started providing additional information regardmental retardation were also prevalent. This study extends previous studies that have reported an neurological disorders is known to arise from the expansion of trinucleotide repeats between generations increased prevalence of certain minor physical abnormalities in schizophrenic patients [22][23][24][25] and suggests of affected individuals. 150 The evidence for dominant inheritance and anticipation, the apparent prevalence that other microdeletions (among other potential etiologies) may be causing the dysmorphic features of dominant genes in schizophrenia as well as the high frequency of human brain genes containing trinucleoidentified.…”
Section: Genetic Approachessupporting
confidence: 89%
“…Recent studies have started providing additional information regardmental retardation were also prevalent. This study extends previous studies that have reported an neurological disorders is known to arise from the expansion of trinucleotide repeats between generations increased prevalence of certain minor physical abnormalities in schizophrenic patients [22][23][24][25] and suggests of affected individuals. 150 The evidence for dominant inheritance and anticipation, the apparent prevalence that other microdeletions (among other potential etiologies) may be causing the dysmorphic features of dominant genes in schizophrenia as well as the high frequency of human brain genes containing trinucleoidentified.…”
Section: Genetic Approachessupporting
confidence: 89%
“…Green et al (1989) found that males with poor pre-morbid functioning were particularly likely to exhibit dysmorphic features, while Waddington et al (1990) reported an association between such anomalies and male sex, cognitive dysfunction, and obstetric complications.…”
Section: Brain Abnormalities In Schizophrenic Malesmentioning
confidence: 99%
“…Several neurological disorders like epilepsy, mental retardation and learning disabilities are associated with the presence of these anomalies. Studies comparing schizophrenic patients with normal controls also found an excess of MPAs in schizophrenics (15,16). In a study correlating MPAs with Wechsler Scale performance a strong correlation of MPAs with lower verbal IQ and poor premorbid adjustment was observed (16).…”
Section: Minor Physical Anomaliesmentioning
confidence: 97%
“…Green et al (15), in a non-controlled study, found MPAs associated with early onset of illness (before age 18). A later study comparing patients with schizophrenic and bipolar disease and family controls found increased prevalence of MPAs among schizophrenic patients, confirming previous associations of these markers with earlier age of onset and lower premorbid adjustment.…”
Section: Minor Physical Anomaliesmentioning
confidence: 98%
See 1 more Smart Citation